Más allá del debate cuantitativo/cualitativo: la necesidad de aplicar metodologías participativas conversacionales - Montañés Serrano, Manuel (Política y Sociedad, 2007)
In this article it is shown that there are no inherent quantitative or qualititave realities, but such characteristics depends on the observant subject. All depends on the stories we can actually depend upon. Being given that the stories match the speaker’s needs. Therefore, we need to apply methodologies aimed at making that all stories —not only the speaker’s— count if we want to understand the social/cultural reality which worries and thus keeps the ensemble of the citizens busy as well as to issue proposals responding to this situation. This will turn the application of conversational participative methodologies into a scientific requirement, in addition to being an ethic demand